INTEGRATING PERSONAL EXPERIENCE (PE) METHOD IN NARRATIVE TEXT: WRITING APPROACH - Hermanses, Sam (Uniqbu Journal of Social Sciences, 2022)
The objective of this articles was to find out whether or not the use of students personal experience method improve writing ability of the eight grade students at SMP Negeri 3 Baranti. This research used pre-experimental method. The population of this research was three classes of the eight grade students at SMP Negeri 3 Baranti in academic year 2017/2018 with the total population were 61 students. The sample of this research was VIII. a (21 students). This sample was taken by simple random sampling technique. This research applied student personal experience (SPE) method. This research applied one kinds of instruments was writing test.The researcher found that by using student personal experience (SPE) method in teaching writing, it could improve the writing ability of the eight grade students at SMP Negeri 3 Baranti. It was proved by P-Value was lower than α (0,000<0,05). So, the researcher stated that H0 was rejected and H1 was accepted. Based on the data analysis, the researcher concluded that student personal experience (SPE) method was effective in improving students’ writing ability at SMP Negeri 3 Baranti.